200k views
5 votes
Match the following items by evaluating the expression for x = -6. x^-2 x^-1 x^0 x^1 x^2

User Adejoke
by
5.3k points

2 Answers

5 votes

Answer:

x = - 6

Explanation:

x = -6x⁻² x⁻¹ x⁰ x¹ x²

x² = 0, x = 0

x¹ = 0, x = 0

the following points are undefined

x = 0

combine undefined points with solutions:

x = - 6

User Oleg Matei
by
5.3k points
0 votes

Answer:

see below

Explanation:

x = -6 ⇒

  • x^-2 = (-6)^-2 = 1/36
  • x^-1 = (-6)^-1 = -1/6
  • x^0 = (-6)^0 = 1
  • x^1 = (-6)^1 = -6
  • x^2 = (-6)^2 = 36
User Alberto Centelles
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.